Familial Reactive Perforating Collagenosis with Adolescence-Onset: A Rare Case Report and Literature Review - Tsaqilah L; Nastiti HA; Usman HA; Avriyanti E; Dharmadji HP; Hidayah RMN (Dove Medical Press, 2024)
Laila Tsaqilah,1 Hedwika Advina Nastiti,1 Hermin Aminah Usman,2 Erda Avriyanti,1 Hartati Purbo Dharmadji,1 Risa Miliawati Nurul Hidayah1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, West Java, Indonesia; 2Department of Anatomical Pathology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Laila Tsaqilah, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Jl. Pasteur No. 38, Bandung, West Java, 40161, Indonesia, Tel/Fax +62 822 8447 4849, Email laila.tsaqilah@gmail.comAbstract: Familial Reactive Perforating Collagenosis (FRPC) is a very rare form of benign dermatosis frequently presented during early childhood and not associated with systemic diseases. Less than 50 FRPC patients have been reported in the literature. Due to the limited number of cases, the pathophysiology of this unique entity remains elusive; moreover, no standard treatment has been agreed upon. Here, we report a case of FRPC in a 20-year-old male who was presented with generalized multiple discrete papules covered with central keratotic plugs in all regions of his body, particularly in the facial area, neck, abdominal, and extensor region of the extremities for more than 7 years. Similar symptoms were acknowledged in the patient's family members. Histopathological analyses identified the crateriform shape invagination in the epidermis filled with inflammatory lymphocytes and basophilic debris and perforated by basophilic collagen bundles from the underlying dermis. Based on the clinical and histopathological findings, the patient was diagnosed with FRPC. He was treated with topical desoximetasone 0.25% cream applied 2- 3 times daily. A follow-up evaluation after 4 weeks revealed a near-complete resolution of skin papules. To our knowledge, this is the first report of FRPC case from Indonesia. Unlike the majority of FRPC patients who had their disease onsets during infancy or early childhood, FRPC skin manifestations in our patient started during the adolescence period. The resolution of skin manifestations after daily application of topical desoximetasone suggests that topical corticosteroids are a potential treatment option for FRPC patients.Keywords: familial reactive perforating collagenosis, benign dermatosis, central keratotic plug, crateriform shape invagination, topical desoximetasone